1997
DOI: 10.1074/jbc.272.39.24145
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin Is a Major Protein Component of Glut4-containing Vesicles

Abstract: In fat and skeletal muscle cells, glucose transporter isoform 4 (Glut4) is translocated to the cell surface in response to insulin via a system of specialized recycling vesicles. Besides Glut4, these vesicles include the novel insulin-regulatable aminopeptidase, receptors for insulin-like growth factor-II/Man-6-phosphate and transferrin, and a glycoprotein with the molecular mass of 110 kDa. We report here by the criteria of the partial protein sequencing and subsequent cDNA cloning that glycoprotein 110, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 22 publications
2
91
0
1
Order By: Relevance
“…These protocols have resulted in the identification of numerous proteins such as VAMP2 (Cain et al, 1992) and sorting receptors such as M6PR (Kandror and Pilch, 1996) and sortillin (Lin et al, 1997;Morris et al, 1998) that one might expect to be involved in vesicular traffic. Importantly and as cited in the introduction, IRAP was also identified in this way as marker for GSV trafficking that is apparently more abundant than GLUT4 itself.…”
Section: Discussionmentioning
confidence: 99%
“…These protocols have resulted in the identification of numerous proteins such as VAMP2 (Cain et al, 1992) and sorting receptors such as M6PR (Kandror and Pilch, 1996) and sortillin (Lin et al, 1997;Morris et al, 1998) that one might expect to be involved in vesicular traffic. Importantly and as cited in the introduction, IRAP was also identified in this way as marker for GSV trafficking that is apparently more abundant than GLUT4 itself.…”
Section: Discussionmentioning
confidence: 99%
“…A function for sortilin in glucose metabolism had been noted early on when the receptor was identified as a major constituent of vesicle carrying the glucose transporter (Glut) 4 48,49 . Following insulin stimulation, Glut4 moves from intracellular storage vesicles to the cell surface to facilitate uptake of glucose in muscle and adipose tissues.…”
Section: Sortilin a Risk Factor For Hypercholesterolemia And Myocardmentioning
confidence: 99%
“…The initial studies identified the insulin-responsive aminopeptidase (IRAP) (11,12) and the sorting receptor, sortilin (15,16), as major proteins components of GLUT4 vesicles that translocate to the cell surface in response to insulin. With the advent of mass spectrometry, numerous additional proteins were identified as constituents of GLUT4-rich vesicles, notably components of the vesicular trafficking machinery (17) such as Vamp2 (13) and motor proteins that might mediate vesicle movement (18) as well as additional cargo proteins such as the receptors for transferrin (TfR) (13) and cation-independent mannose 6-phosphate (CIM6PR) (13,18).…”
mentioning
confidence: 99%